Determinan kebijakan dividen: Peran profitabilitas, leverage, dan ukuran perusahaan pada perusahaan LQ45 di Indonesia - Mamahit, Tiara Angelica; Budiarso, Novi Swandari; Kapojos , Peter Marshall (Riset Akuntansi dan Manajemen Pragmatis, 2025)
This study examines the effect of profitability, leverage, and firm size on dividend policy in companies listed in the LQ45 Index on the Indonesia Stock Exchange for the 2022–2024 period. Profitability is measured by Net Profit Margin (NPM), leverage by Debt to Assets Ratio (DAR), firm size by the natural logarithm of total assets, and dividend policy by Price Earnings Ratio (PER). The research employs a quantitative approach using secondary data with purposive sampling, resulting in 27 companies from a population of 45. Data were analyzed using multiple linear regression. The results indicate that firm size significantly influences dividend policy, while profitability and leverage have no significant effect. Simultaneously, profitability, leverage, and firm size collectively affect dividend policy. These findings imply that larger firms tend to have more stable financial performance and greater capacity to distribute dividends compared to smaller firms, while profitability and leverage alone are insufficient to determine dividend distribution decisions.